The Effect of Board of Directors’ Characteristics on Payout Policy: An Empirical Study on Saudi Banks - Mukhaymar, Haifa; Aljughaiman, Abdullah (The Arab Journal of Administration, 2024)
This study seeks to know the impact of the board of directors’ characteristics on the dividend policy. The study was conducted on a sample of (10) banks listed in the Saudi market for the period (2010-2020). To achieve the objectives of the study, this paper used an unbalanced panel data approach to analyze our data sample. The results of the study show a positive association between the board of directors’ characteristics, (i.e., the size of the board of directors, independence of members) and the payout ratio. These findings are in line with agency cost theory, which asserts that effective corporate governance leading to prevent managers from taking self-interests decision and providing stronger monitoring over top-management activities. Furthermore, the paper shows negative significant association between busy board (measured by multi-membership percentage of the board and payout ratio. This result is supported by the busy hypothesis, which argues that busy members would not be able to provide effective advice and their monitoring ability is weak. This might happen because of the extensive works and duties they have across their memberships. The implication of this study assure that it is important to apply best corporate governance practices to achieve the shareholders goals. In other words, banks in Saudi need to monitor the board of director characteristics, specifically board size, independence, and multi-membership.